A Case of Hepatic Glomerulosclerosis with Monoclonal IgA1-κ Deposits. (1st October 2018) - Okabayashi, Yusuke; Tsuboi, Nobuo; Nakaosa, Naoko; Haruhara, Kotaro; Kanzaki, Go; Koike, Kentaro; Shimizu, Akihiro; Fukui, Akira; Okonogi, Hideo; Miyazaki, Yoichi; Kawamura, Tetsuya; Ogura, Makoto; et al.
Abstract : Glomerular immunoglobulin A (IgA) deposition is a common finding in hepatic glomerulosclerosis; thus, this disease is also called hepatic IgA nephropathy. However, only a small number of patients with hepatic IgA nephropathy have active glomerular lesions, so functional decline is slow in most cases. In this report, we describe a 60-year-old man who developed nephrotic syndrome and progressive renal impairment during follow-up for alcoholic liver cirrhosis. A renal biopsy showed a membranoproliferative glomerulonephritis-like pattern; diffuse double-contours of the glomerular basement membrane and focal active glomerular lesions with moderate-to-severe endocapillary proliferation and fibrocellular crescents. Immunofluorescence findings revealed granular staining for monoclonal IgA1- κ and C3 on the peripheral capillary walls. Laboratory examinations did not reveal any definitive evidence of myeloproliferative disorders. Therefore, this case may represent a previously unrecognized etiology of renal injury in relation to liver cirrhosis that is characterized by monoclonal IgA1- κ deposits and proliferative glomerulonephritis.